Antibacterial Activity of N-Hexan and Ethyl Acetate Fractions of Gaharu (Aquilaria Malaccensis) Leaves against Bacteria that Cause Infection - Yahya, Fifi Adelia; Herwin, Herwin; Fitriana, Fitriana (Journal Microbiology Science, 2024)
Gaharu (Aquilaria malaccensis) leaves contain alkaloids, terpenoids, flavonoids, saponins, and tannins that can help cure infections. This study aims to determine the antibacterial activity of n-hexane and ethyl acetate fractions of Gaharu leaves against skin infection bacteria such as Propionibacterium acnes, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis by Bioautography-TLC. Gaharu leaves symplisia was extracted using the maceration method using ethanol 96% solvent and fractionation with solid-liquid method to obtain n-hexane and ethyl acetate fractions. The result of the screening antibacterial activity of n-hexane and ethyl acetate fractions of Gaharu leaves with concentrations of 0,5% active to 4 bacteria test. The results of antibacterial activity n-hexane and acetaet ethyl fraction by Bioautography-TLC using n-hexane:ethyl acetate (1:4) eluent showed Rf 0.67 and Rf 0,16 value in the n-hexane fraction and an Rf 0.78 value in the ethyl acetate fraction active to 4 bacteria test.  The identification results of the chemical compound of the n-hexane fraction contain flavonoids and tannins (AlCl3 and FeCl3 reagents.), the ethyl acetate fraction contains flavonoids ( AlCl3 reagents).